Strategic management of health care organizations - Ginter, Peter M.; Duncan, W. Jack [ (Walter Jack)]; Swayne, Linda E. (Jossey-Bass, 2013)
A structured strategic management approach is what's needed to tackle the revolutionary change the health care system has been experiencing. Today, health care organizations have almost universally embraced the strategic perspective first developed in the business sector and now have developed strategic management processes that are uniquely their own. Health care leaders have found that strategic thinking, planning, and managing strategic momentum are essential for coping with the dynamics of the health care industry. Strategic Management has become the single clearest manifestation of eff